Cegah Perudungan dengan Pengembangan Potensi Warga Belajar di PKBM Yabes Medan - Lisbet Rizona Br Sianturi; Bengkel Ginting; Fajar Utama Ritonga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2024)
Community Learning Activity Center (PKBM) is a non-formal education unit organized to meet various learning needs of the community established and managed by the community in an effort to empower local communitie. The purpose of this writing is to prevent bullying with the development of the potential of residents studying at PKBM Yabes Medan. The location of the practice is on Jl. Jamin Ginting GG. Build Sangka Manuk No. 8, Kel. Mangga, Kec. Medan Tuntungan, Medan City, North Sumatra. With the focus of the research subject on learning citizens. With a period of practice for 4 months. The method used in this practice is the groupwork method proposed by Zastrow with stages consisting of: (1) Engangement, Intake and Contract, (2) assessment, (3) Planning, (4) Intervention, (5) Monitoring, (6) Evaluation, and (7) Termination. The results of this practice show an increase in client knowledge in English language skills, basic computer operating skills and character. However, clients in a condition are vulnerable to bullying actions beyond their control. This is the result of previous habits. So evaluation and supervision are needed as a reminder so that clients can control themselves.